Physiological responses of cereals of agronomic interest to arthropod herbivory stress - Laura Viviana Arias-Porras; Cristhian Camilo Chávez-Arias; Mateo Bejarano-Hernandez; Helber Enrique Balaguera-López (Plant Stress, 2023)
Cereals, such as rice, wheat, corn, and sorghum, are important staples for billions of people worldwide. Biotic stress caused by pest arthropod herbivory is one of the main factors that reduces crop production and yield. Worldwide, cereal crop losses due to damage caused by arthropod pests can exceed 10 %. In response to the attack, plants present a series of physiological responses that affect primary processes such as compensatory effects in photosynthesis and different responses in respiration. Likewise, plant hormones (e.g. jasmonic acid and salicylic acid) are involved in the signaling of defense mechanisms in plants, whether in the form of physical resistance (e.g. production of trichomes and waxy cuticles), or chemical resistance mostly mediated by secondary metabolites such as terpene and phenol classes, either directly or indirectly effects. Additionally, resources, such as carbon and nitrogen, are reallocated to the sink or defense response. This review provides information on the physiological responses of plants to the presence of some arthropod pests of interest in the main cereals worldwide.